Community Feeling and Narcissism as Two Opposite Phenomena - Kałużna-Wielobób, Alina; Strus, Włodzimierz; Cieciuch, Jan (Frontiers in Psychology, 2020)
The objective of the current study was to examine the relations between narcissism and Adler’s community feeling. Based on theoretical considerations, we claim that community feeling can be treated as be an opposite pole of narcissism and we expected that: (1) both grandiose and vulnerable narcissism would be negatively related to community feeling and that (2) grandiose and vulnerable narcissism would be positively related to anti-community domination and isolation. A sample of 520 university students (Mage = 21.37, SDage = 4.31) completed the Community Feeling Questionnaire (CFQ), the Narcissistic Admiration and Rivalry Questionnaire (NARQ) and the Hypersensitive Narcissism Scale (HSNS). Structural equation modelling largely conformed our expectations. These results suggest that narcissism can be understood in terms of community feeling deficit. It turned out that community feeling and narcissism are related constructs but they are not reducible to each other.